A reply to Douze and Delagnes's 'The pattern of emergence of a Middle Stone Age tradition at Gademotta and Kulkuletti (Ethiopia) through convergent tool and point technologies' [J. Hum. Evol. 91 (2016) 93–121]. Issue 125 (December 2018) - Sahle, Yonatan; Braun, David R.
Abstract: Douze and Delagnes (2016) revisit Middle Stone Age (MSA) lithic assemblages from the Gademotta Formation (Fm.), Ethiopia. Their analysis of selected assemblages from three of the 1972 excavations expands the original typo-technological interpretations by Wendorf and Schild (1974). We particularly welcome their evaluation of our recent inferences about the function of pointed artifacts and technological patterns in the Gademotta Fm. (Sahle et al., 2013, 2014). However, we find several arguments and conclusions in Douze and Delagnes (2016) to be rather unconvincing and irreconcilable with results from analyses of whole assemblages (Wendorf and Schild, 1974; Sahle et al., 2013, 2014). Specifically, their summary attribution ofall early MSA burin-like fractures on the distal tips of pointed artifacts to intentional resharpening blows, and their use of this pattern as a technological "chrono-marker" unique to the region are untenable. Here, we highlight these issues in the hopes of a clearer understanding of the evident technological patterns in the Gademotta Fm.